2013
DOI: 10.1097/opx.0000000000000001
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Ophthalmic Questionnaires

Abstract: This review provides a descriptive catalog of ophthalmic PRO instruments to inform researchers and clinicians on the choice of the highest-quality PRO instrument suitable for their purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
242
2
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(259 citation statements)
references
References 104 publications
7
242
2
8
Order By: Relevance
“…Refractive corrections generally reduced these limitations. However, specific issues were affected by type of correction, for example wearing thick rimmed glasses reduced peripheral vision making driving difficult (quotes [11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Refractive corrections generally reduced these limitations. However, specific issues were affected by type of correction, for example wearing thick rimmed glasses reduced peripheral vision making driving difficult (quotes [11][12][13][14][15][16][17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…18 Ideally, patient consultation through in-depth interviews or focus group discussions is one of the most important stages of developing the content of a high quality patient-reported outcome (PRO) instrument. 14,15 Surprisingly, these preceding qualitative studies have not been discussed or published in detail for any of the publication that reported the development of the existing refractivespecific PRO instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose the CVAQC for this study because it has a content that primarily focuses on school activities, and possesses excellent psychometric properties 7. Moreover, a recent study demonstrated that a meticulously translated CVAQC in the Turkish language formed a valid and reliable measure with robust psychometric properties 15.…”
Section: Discussionmentioning
confidence: 99%
“…Several PROs have been developed for children with visual impairment 2 9–14. Among all existing PROs, the Cardiff Visual Ability Questionnaire for Children (CVAQC) is considered as one of the highest quality PRO tools in terms of psychometric properties and content coverage 7. The CVAQC assesses the impacts of visual impairment in daily living activities with a special focus on school activities.…”
Section: Introductionmentioning
confidence: 99%